2017
DOI: 10.1371/currents.dis.c0c84b1b680388649227be71823e6adf
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Veterans Health Administration Emergency Management Research Agenda

Abstract: Introduction: The Veterans Health Administration (VHA), the largest integrated healthcare delivery system in the United States, is charged with ensuring timely access to high-quality care for veterans during disasters, and supporting national, state, local, and tribal emergency management and homeland security efforts. In 2008, the VHA Office of Public Health (OPH) sponsored the first VHA Emergency Management Research Agenda-setting conference to develop research priorities that address the needs of veterans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…healthcare missions is to provide backup medical resources to both the military health system and to local communities following terrorist incidents and other major disasters [29]. As such, VA has responded to numerous national emergencies [30] and also provided care for non-Veterans during such events [30][31][32][33]. Nevertheless, we found that 57-70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…healthcare missions is to provide backup medical resources to both the military health system and to local communities following terrorist incidents and other major disasters [29]. As such, VA has responded to numerous national emergencies [30] and also provided care for non-Veterans during such events [30][31][32][33]. Nevertheless, we found that 57-70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…In November 2009, the White House issued the National Strategy for Countering Biological Threats to manage the risks from naturally occurring and deliberately introduced diseases. The US biosurveillance system has tried to encompass human-, animal-, and plantrelated health for a "full-spectrum type threat" (Dobalian et al, 2017;Koenig, 2003). More than 4,000 surveillance sites in more than 30 major US cities have been established with an international biosurveillance network that impacts at least 92 countries (Larkins et al, 2020;Russell et al, 2011).…”
Section: Type IImentioning
confidence: 99%